Salted herring brine as a coating or additive for herring (Clupea harengus) products — A source of natural antioxidants?. (October 2016) - Albertos, Irene; Gringer, Nina; Rico, Daniel; Baron, Caroline P.
Abstract: The objective of this study was to characterise herring brine and assess its use as natural antioxidant in herring preservation. Herring brines from different marinated products (brine from fillet-ripened spice-cured herring SC, traditional barrel-salted spice-cured herring TSp and brine from traditional barrel-salted herring TSa) were used without any pre-treatment or with a previous pH adjustment, and tested either as coating agents (glazing) for frozen herring or additives in fresh mince herring, in order to prevent oxidation. TSa and TSp were the most effective glazing agents, retarding lipid oxidation. Brines tested as additive retarded lipid and protein oxidation in a similar trend than herring mince containing salt and/or protein. SC brine was more efficient against lipid and protein oxidation when compared to the other tested brines. Using protein fractions isolated from herring marinating brines as glazing or additive seems feasible for preventing oxidation of both frozen and fresh herring. Highlights: All brines were more effective antioxidants than water glazing in frozen herring. All brines delayed lipid and protein oxidation in fresh herring mince. Alkali pH-shift of brines did not produce any advantages compared to unmodified pH. TSa and TSp glaze showed antioxidant potential as shown from volatile and PV values. SC was effective as antioxidant in fresh herring mince.